Erector Spinae Plane block: evaluation of its efficacy as a component of multimodal anaesthesia in open kidney surgery - P. M. Kayumova; Sh. I. Giyasov; M. B. Krasnenkova; A. N. Musabaev (Вестник урологии, 2024)
Introduction. Currently, the Erector Spinae Plane (ESP) block is widely used both as an independent method of anesthesia and as a component of multimodal anesthesia. It creates an extensive sensor block, spreads over 5 – 7 spinal segments.Objective. To evaluate the efficacy of ESP block as a component of multimodal anesthesia during open kidney surgery.Material & methods. The studies were conducted on 116 patients of ASA class I – III at the age of 18 – 85 years All patients were performed inhalation anesthesia with Isoflurane. NSAID (Diclofenac 75 mg IM) was administered as pre-emptive analgesia. In the Study group (n = 60), after tracheal intubation and positioning, an ESP block was performed under ultrasound control at the Th-9 level with a 0.5% Sol. Bupivacaine (25 – 30 ml). In the Control group (n = 56), only inhalation anesthesia was performed. Pain severity, opioid consumption frequency (Sol. Promedoli), postoperative nausea and vomiting were assessed in the postoperative period. A numeric rating scale (NRS) was used to assess pain, which was recorded every 6 hours during the day.Results. Patients in the study group showed a low assessment of postoperative pain on the numeric rating scale compared to the Control group (p < 0.001). The consumption of opiates (Sol. Promedoli) was also lower, especially in the first 6 hours after surgery (p < 0.001).Conclusions. The results of our studies confirmed the efficiency of ESP block by reducing the consumption of opiates and NSAIDs. The main advantage of this method is its ease of implementation and safety.